Reproductive Biology of the Sea Cucumber Holothuria mammata (Echinodermata: Holothuroidea) - Eliana Venâncio; Pedro M. Félix; Ana C. Brito; Francisco Azevedo e Silva; Tomás Simões; João Sousa; Susana Mendes; Ana Pombo (Biology, 2022)
Holothuria mammata is one of the most valuable species of sea cucumber, as well as one of the main target species harvested in the Mediterranean and NE-Atlantic regions. This study aims to describe the reproductive cycle of H. mammata in a coastal area of southwest Portugal. Monthly samplings were carried out for 19 months, with the concomitant collection of environmental data and biometric data. H. mammata had a sex ratio of 1:1.2 (male:female) and a size at first maturity of 142 mm for males and 167 mm for females. The gonadosomatic index (GI) peaked between April and May for both sexes. Gonad development started when days had a shorter photoperiod (9 to 13 h of sunlight) and lower seawater temperature (<15 °C), and spawning occurred later, with longer photoperiod (13 to 15 h of sunlight) and higher seawater temperature (>15 °C) and chlorophyll-a concentrations. The development of new studies to increase the biological and ecological knowledge of the populations of H. mammata is essential to create conditions for the domestication of broodstock in captivity, to allow the development of fishing regulations based on informed decisions and to create precise measures for the conservation of ecosystems.